Study of hydroacoustic signals in aquaculture as a tool to improve fisheries efficiency - Kartsan Igor; Lutsyshen Vitaly; Nerush Alena; Tuzov Nikolai (E3S Web of Conferences)
The article is devoted to the application of special methods for estimating the informativity of hydroacoustic signals, which will make it possible to study a wide range of oscillatory signals, including multiharmonic and transient ones. In the process of research will be used methods of spectral analysis, cepstral analysis, subband analysis, wavelet analysis and anomaly analysis. These approaches will assist not only in accounting for fish abundance in aquaculture cages, but also in estimating fish health and biomass, which is critical for effective aquaculture resource management.